Oral health in professional Slovak soccer players: Assessment of dental risks, subgingival microbiota and genetic influences - Silvia Timkova; Veronika Martinska; Andrea Madarasova Geckova; Vladimir Elias; Michal Konecny; Peter Kizek (PLoS ONE, 2026)
Background Recent studies reveal high rates of dental issues among professional soccer players, worsened by poor hygiene, frequent sport drinks consumption and limited preventive care. Busy schedules, frequent relocations and changing clubs further disrupt dental routines, impacting performance and well-being. Therefore, we decided to assess the oral health status of professional Slovak soccer players and address these critical concerns. Methods We assessed the oral health of 51 male soccer players from two elite Slovak soccer clubs during 2023/2024 season. Data collection included two paper-based questionnaires and a clinical oral examination by dentists. Additionally, clinical laboratory data were collected from saliva to test for presence of periopathogenic bacteria and DNA polymorphisms. Results Although 92.2% had valid health insurance, 36% did not attend dental check-ups in the past year, indicating underutilization of preventive care. While 86.2% brushed their teeth more than twice daily, only 48% practiced interdental cleaning and 35.3% used mouthwash. A significant 83.7% consumed sports drinks high in sugar and acid, influencing oral health risks. Clinical examinations revealed that 86.3% had a moderate to high DMF index (mean decayed teeth: 3.8) and 54.9% exhibited gingivitis. Bacterial analyses showed 25.5–74.5% carried highly periopathogenic bacteria, indicating a high risk for periodontitis. Additionally, 15.7% of players exhibited presence of DNA polymorphisms associated with risk of periodontitis onset. Conclusion This study reveals a gap in preventive dental care among professional soccer players, emphasizing the urgent need for integrated oral health strategies within sports programs.